Analysis of the Global Structural Strength of a 35,000 DWT Single Point Mooring (SPM) Buoy Under Wave Loads - Elsa Rizkiya Kencana; Muhammad Fatkhurrozi; Alvin Aziz Nugraha; Olga Wulandari Kelen (Department of Ocean Engineering, 2024)
Single Point Mooring (SPM) systems are offshore structures facilitating cargo transfer between tankers and refineries in deeper waters to accommodate larger vessels. The marine environment at SPM sites often features unstable and extreme wave conditions, making it essential to understand the SPM's response to these forces. SPMs include an anchor system with mooring lines secured to the seabed. Evaluating the stress on these lines and the buoy structure under environmental loads is crucial. This research models the SPM structure using dimensional data and mooring line specifications. The hypothesis posits that, based on the significant wave height and 100-year wave period in the Balongan Sea, as well as the minimum breaking load value for a 35,000 DWT SPM, the maximum tension in the mooring lines is 956 kN, which is below 2261 kN. It means safe based on API RP 2KS (2005) standards. Thus, the mooring lines are safe during operations under 100-year environmental loads with a maximum tension of 1732 kN. The maximum stress on the SPM buoy structure is 1.87 MPa and 3.38 MPa in ULS and ALS conditions, respectively.